Penerapan Model Pembelajaran Problem Based Learning (PBL) Pada Materi Reaksi Asam Basa Terhadap Hasil Belajar Siswa Di SMK Negeri 1 Biaro - reity feronika Manenda; Soenandar Tengker (Chemistry Department, Universitas Negeri Manado, 2023)
The aim of the research was to find out the difference in learning outcomes before and after applying the Problem Based Learning (PBL) learning model to the acid-base material of class X Agriculture SMK Negeri 1 Biaro. This research was conducted in class X Agriculture at SMK Negeri 1 Biaro in the 2022/2023 academic year. A total of 16 students of class X Agriculture were selected as the research sample. Based on the test data for the hypothesis t test, a tcount value of 38.077 is obtained with a ttable value of 2.042. And the significant level used is α = 0.05 with degrees of freedom n1 + n2 - 2 (16+16-2) = 30. By looking at the values ​​of tcount and ttable, tcount > ttable means that H0 is rejected and H1 is accepted. Based on the increase test (N-gain) obtained 0.75 with high criteria. Thus it can be concluded that the Application of the Problem Based Learning (PBL) Learning Model on Acid-Base Reaction Material has an effect on Student Learning Outcomes at SMK Negeri 1 Biaro.